(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
A total of 282 moss species that represent 107 genera, 42 families, 18 orders, 5 classes and 3 divisions compose the bryoflora in the steppe zone of Ukraine. Division Anthocerotophyta consists of 1 species. Division Hepatophyta is represented by 30 species, 15 genera, 13 families, 3 orders and 2 classes. Class Marchantiopsida has the biggest number of species – 19 species of 6 genera and 4 families. Class Jungermanniopsida is represented by 11 species, 9 genera and 9 families only. Division Bryophyta consists of 251 species, 99 genera, 27 families, 14 orders and 2 classes. Class Sphagnopsida has only 15 species. Class Bryopsida consists of 236 species, 89 genera, 41 families and 18 orders. 29 moss species have 38 infra-species taxa, namely 14 varietes and 24 forms. The most species-rich familiesare Pottiaceae (51 species), Bryaceae (32 species), Brachytheciaceae (24 species). Among the main genera are Bryum (26 species), Sphagnum (15 species), Orthotrichum (14 species), Riccia (14 species) Tortula (13 species).